The Effectiveness of Learning the Socio-Drama Method in Class III Elementary School Islamic Education Subjects: Efektifitas Pembelajaran Metode Sosio Drama pada Mata Pelajaran Pendidikan Agama Islam Kelas III SD - Darma Andika (International Journal of Technology Vocational Education and Training, 2020)
Islamic religious education is a basic subject and is prioritized in the process of educating students. . Based on the results of the study, it was found that in the experimental group, there were 22 students (88%) who had complete scores and in the control group, there were 16 people (64%) who had complete scores and based on the comparison there was a P- Value sebnayak 0.001 <0.005, which means that there is a difference in the effective learning method of the socio-drama material of the Prophet's story in the Islamic religious education class III where the average score is higher, which is 95.23 in the experimental group when compared to the average value. namely as many as 85.53 in the control group.